Disfagia e.c Globus Histerikus - Indra Zachreini; Rizki Fadilah Harahap (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Dysphagia is a disorder in the process of swallowing with the sensation of stopping a bolus of food when swallowing. Dysphagia is not a disease, but a symptom. Globus hystericus is one of the etiologies of dysphagia. Globus hystericus, also known as globus pharyngeus or globus sensation, is a description of a subjective feeling in the presence of a lumpy mass that results in persistent or intermittent discomfort in the esophagus or throat. These sensations can cause difficulty swallowing or breathing which can become worse. This situation lasts a long time and often recurs after treatment. The number of globus hystericus incidents that come to the ENT specialist is 3-4% with 46% of them in healthy condition. Enforcement of the diagnosis of globus hystericus is obtained through anamnesis, physical examination and supporting examinations. Treatment of globus hystericus is carried out over a long period of time and requires patient persistence in carrying out therapy in order to achieve the target. This paper is expected to help find out how to manage dysphagia due to globus hystericus.